Uczeń ze specjalnymi potrzebami edukacyjnymi na lekcji języka obcego w szkole podstawowej – rola nauczyciela i środowiska szkolnego w realizacji koncepcji inkluzji - Janicka, Monika (Neofilolog, 2017)
The article presents the tenets of the inclusion concept and the ways as well as the problems concerned with its implementation. Special attention has been given to primary school-students with special educational needs in the language classroom. In the article results of a research project are presented. The project had two aims. The first was to elicit the level of implementation of the inclusion concept at Polish primary schools using the example of teaching foreign languages. The other aim was to sensitise the students of applied linguistics – future language teachers – to the challenges concerned with teaching languages to children with special educational needs.